Community-Based Management and Interrelations between Different Technology Adoption Decisions: Innovations in Village Poultry Farming in Western Africa - Epiphane Sodjinou; Arne Henningsen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2012)
Community-based management (CBM) of village poultry aims to foster development and reduce poverty in Benin by disseminating five technologies for improving village poultry farming. We develop a theoretical model to analyze multiple technology adoption decisions that takes into account the interrelations between the technologies. Estimates from multivariate probit models indicate significant interrelations between the five adoption decisions. We show how the estimation results, and particularly the different types of marginal effects, can be utilized to deeply analyze the interrelations between adoption decisions. CBM successfully promoted the adoption of various technologies. Some adoption decisions indicate farmers' general openness towards new technologies.
Keywords: Q12; Q16; C31; C35; O13; O14; 330; Community-Based Management; Technology adoption; Multivariate probit; Village poultry; Benin; West Africa